2021
DOI: 10.1371/journal.pone.0256429
|View full text |Cite
|
Sign up to set email alerts
|

Add-on effect of Chinese herbal medicine in the treatment of mild to moderate COVID-19: A systematic review and meta-analysis

Abstract: Introduction Coronavirus disease 2019 (COVID-19) has emerged as a global pandemic since its outbreak in Wuhan, China. It is an urgent task to prevent and treat COVID-19 effectively early. In China’s experience combating the COVID-19 pandemic, Chinese herbal medicine (CHM) has played an indispensable role. A large number of epidemiological investigations have shown that mild to moderate COVID-19 accounts for the largest proportion of cases. It is of great importance to treat such COVID-19 cases, which can help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Significant effects of the combined therapy of herbal medicine with Western medicine has been found, and this have revealed the potential role of herbal medicine in treating COVID-19 (Ang et al, 2020) [6] . In this regard, highquality clinical trials are needed to evaluate the efficacy and safety of herbal medicine or medicinal plants combined with conventional therapy in the treatment of adults with mild to moderate COVID-19 in the future (Du et al, 2021) [21] . Some, prelimentary studies hve been condiucted in some these plants, thus, some of them may acceptable preventive measure against COVID-19 infection to boost immune system cells and to repress the production and secretion of proinflammatory cytokines as well as an adipose tissue derived hormone leptin having the proinflammatory nature.…”
Section: Resultsmentioning
confidence: 99%
“…Significant effects of the combined therapy of herbal medicine with Western medicine has been found, and this have revealed the potential role of herbal medicine in treating COVID-19 (Ang et al, 2020) [6] . In this regard, highquality clinical trials are needed to evaluate the efficacy and safety of herbal medicine or medicinal plants combined with conventional therapy in the treatment of adults with mild to moderate COVID-19 in the future (Du et al, 2021) [21] . Some, prelimentary studies hve been condiucted in some these plants, thus, some of them may acceptable preventive measure against COVID-19 infection to boost immune system cells and to repress the production and secretion of proinflammatory cytokines as well as an adipose tissue derived hormone leptin having the proinflammatory nature.…”
Section: Resultsmentioning
confidence: 99%
“…To date, 21 systematic reviews have been identified that have similar findings to this current review ( Liu M. et al, 2020 ; Ang et al, 2020 ; Sun CY. et al, 2020 ; Xiong X. et al, 2020 ; Fan et al, 2020 ; Pang et al, 2020 ; Zeng et al, 2020 ; Zhou et al, 2020 ; Wang H. et al, 2021 ; Liu M. et al, 2021 ; Wang Q. et al, 2021 ; Du et al, 2021 ; Fan et al, 2021 ; Jiang et al, 2021 ; Li et al, 2021 ; Liang et al, 2021 ; Luo et al, 2021 ; Wu et al, 2021 ; Yan et al, 2021 ; Yin et al, 2021 ; Zhuang et al, 2021 ). The treatment of COVID-19 benefits from the rapid dissemination of evidence, providing data for the synthesizing of evidence disseminated was constantly complied by systematic reviewers, resulting in a large number of systematic reviews with overlapping evidence, each article updated with the inclusion of only one or two additional studies at the time of publication.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial involving Nigella sativa supplement to investigate its efficacy in mild symptomatic COVID‐19 patients is ongoing (Koshak et al, 2020 ). A recent systematic review also highlighted those Chinese herbal medicines can be used in the treatment of mild to moderate COVID‐19 and they are very effective in the reduction of symptoms of fever and cough in COVID patients (Du et al, 2021 ). The illustration (Figure 1 ) shows the role of Nutraceuticals in the management of COVID‐19.…”
Section: Nutraceuticals and The Management Of Covidmentioning
confidence: 99%